Effects of subtanstium estrus cow serum with fetal calf serum on culture bovine embryos produce in vitro - M.A. Setiadi .; J. Peli .; K. Schellander . (Hemera Zoa, 1995)
The development capacity of bovine oocytes matured in vitro was investigated by replacement culture medium composition from Estrus Cow Serum (ECS) to Fetal Calf Serum (FCS). The experiment was devided into four groups : group (A) culturedin Medium with ECS and groups (B), (C) and (D) cultured 1, 2 and 3 days in ECS, respectively and the rest of the culture period in medium containing FCS. The results of the experiment show that no significant differences on cleavage rates were observedwithin the experimental groups, but blastocyst development showed significant diferences with the highest rates in group D.